Integrasi Nilai Al-Quran dan Hadits dalam Membangun Karakter Mulia di Era Society 5.0 di SMP IT Nurul Ilmi - Nurul Chairani. P; Danny Abrianto; Bahtiar` Siregar (Medan Resource Center, 2025)
This study aims to examine the novelty and model of integrating Qur’anic and Hadith values in shaping students’ noble character in the Society 5.0 era at SMP IT Nurul Ilmi. Unlike previous studies that generally discuss Islamic character education conceptually, this research offers a contextual model of value integration implemented systematically at the junior secondary level in response to digital-era moral challenges. This study employed a descriptive qualitative approach involving 12 informants consisting of the principal, 4 Islamic education teachers, 3 homeroom teachers, and 4 students. Data were collected through in-depth interviews, participatory observation, and document analysis. The data were analyzed using the Miles and Huberman interactive model, including data condensation, data display, and conclusion drawing and verification. The findings reveal a structured integration model consisting of three main components: (1) Qur’an-based classroom instruction integrating verses and Hadith into subject learning; (2) character habituation programs such as daily Qur’an recitation, congregational prayer, honesty canteen, and digital ethics mentoring; and (3) teacher role modeling reinforced by parental collaboration through monitoring books and digital communication platforms. The character indicators observed include consistent participation in congregational prayer, reduced disciplinary violations, active peer cooperation (ta’awun), and responsible use of digital devices. This study contributes a practical integration framework of Qur’anic and Hadith values that is contextually adapted to the Society 5.0 era, offering a replicable model for Islamic-based schools seeking to strengthen character education amid technological advancement.